"Half‐folded" pedicled scapular bone flap for nonunion after humeral neck fracture: A case report. Issue 6 (28th March 2017) - Matsumae, Gen; Motomiya, Makoto; Watanabe, Naoya; Iwasaki, Norimasa
Abstract : Treatment of a nonunion of the proximal humerus remains a challenge because of the small proximal fragment and poor central cancellous bone stock of the humeral head. In this report, we describe our experience using a "half‐folded" pedicled scapular bone flap with an anatomical locking plate to treat an atrophic nonunion of the proximal humerus in a 64‐year‐old right‐handed woman. The patient had fallen and experienced a common humeral neck fracture 2.5 years previously. During the operation, we elevated the pedicled scapular bone flap, which measured 8.0 cm long and 1.5 cm wide, with a vascular pedicle about 10 cm long. We modified the bone flap to the half‐folded type to fill the massive bone cavity in the humeral head. The proximal tip of the flap was divided into two segments while keeping the ventral soft tissue intact. The grafted bone bridging between the head and shaft of the humerus was rigidly fixed with a plate and screw. The operated shoulder was fixed with a sling and a chest belt for 3 weeks, after which the patient began active motion exercises of the shoulder joint. The flap survived without serious donor site morbidity, and good bone healing was obtained about 3.5 months after surgery. The patient was able to use the shoulder comfortably in daily activity without any serious donor site morbidity at 16 months after the surgery. This procedure may be effective in treating nonunion of the proximal humerus with a massive bone cavity in the humeral head.